Nyanyian rakyat Bugis: Kajian bentuk, fungsi, nilai, dan strategi pelestariannya - Amaluddin, Amaluddin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
Buginese Folksong is a cultural product of Buginese ethnic. As a cultural product, it has been used as a medium of art expression to convey various things on Buginese life, as an addition to the people entertainment medium. This research is fo- cused on four aspects, namely (1) the form, (2) the function, (3) the value, and (4) the defensive or perpetuation strategy. This research includes a qualitative research which employs hermeneutics theory. Based on the result on the research it was found the Buginese Folksong in form of Makkacaping and Elong, that function as the critical media in the social life of Buginese society and contain philosophical, religious, and sociological values.